(untitled) - Marmel, Eaine (Indianapolis, 2016)
This book provides the ideal rundown of Microsoft Office's full feature set and capabilities. Even experienced users may learn something they never realized they were missing. If you need to get things done with minimal interruption to your workflow, Office Simplified will get you up to speed quickly and easily.
Keywords: Phần mềm văn phòng,Office software; Chương trình máy tính,Computer programs